Cinnamon: A potent nutraceutical agent for the protection of the cardiovascular system - Taherah Mohammadabadi; Asif Ur Rehman; Rajesh Jain (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2024)
Diseases such as diabetes, atherosclerosis, and hypertension are risk factors for Cardiovascular Diseases (CVDs). About 17.3 million deaths worldwide were due to CVDs in 2013 and is anticipated to be 23.3 million by 2030. Common therapies for CVDs are associated with wide side effects. Thus, herbal medicines have been regarded more due to fewer side effects, availability, cultural beliefs, and being cheap. For thousands of years, herbal medicine has been used for bacterial infections, colds, coughs, and CVDs. Cinnamon bark contains phenolic compounds such as cinnamaldehyde and cinnamic acid with protective properties that can reduce the risk of cardiovascular diseases, cardiac ischemia and hypertrophy, and myocardial infarction. Furthermore, cinnamon has antioxidant and anti-inflammatory properties and exhibits beneficial effects on the complications of diabetes, obesity, hypercholesterolemia, and hypertension which cause CVDs. Although the protective effects of cinnamon on the heart have been reported in many studies, it needs more clinical studies to prove the pharmaceutical and therapeutic efficacy of cinnamon on risk factors of CVDs. This review explains the protective effects of bioactive compounds of cinnamon on the cardiovascular system.